The role of family support and internal locus of control in entrepreneurial intention of vocational high school students - Dewi Niki Annisa; Fatwa Tentama; Khoiruddin Bashori (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study examined the relationship between family support and internal locus of control with entrepreneurial intention among grade XII students attending Muhammadiyah 3 Vocational High School. From 172 grade XI students attending the school, 93 were selected to participate in the study. This study used a cluster-sampling technique. The data was collected using the entrepreneurial intention scale, the family support scale, and the internal locus of control scale. Multiple regression techniques were used to analyze the data on SPSS 19.0. The results indicated very significant positive relationship between family support and internal locus of control with entrepreneurial intention, family support with entrepreneurial intention, and internal locus of control with entrepreneurship intention. Thus, it can be inferred that the contribution of internal locus of control to entrepreneurial intention is more dominant than family support's contribution.